Digital Marketing Strategy Through Instagram And Tiktok Social Media Platforms In Increasing Sales At PT. Akasa Kreasi Bersama - Afni Suhaida; Rukmini Rukmini; Suhaila Husna Samosir; Feni Damayanti; Intan Ramadhani; Muhammad Rizaldyi Wibowo (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
The development of digital technology has encouraged companies to utilize digital marketing to increase competitiveness and sales. This research analyzes digital marketing strategies through the social media platforms Instagram and TikTok at PT. Akasa Kreasi Bersama. Both platforms have the advantage of reaching a wider audience and increasing interaction with consumers through visual content and short videos. The research method used is descriptive qualitative with data collection techniques through interviews, observation and document study. The research results show that Instagram is effective in building a brand image through its Stories, Reels and IGTV features, while TikTok excels in spreading content virally thanks to its interaction-based algorithm. The use of paid advertising and collaboration with influencers also contributes to increasing sales conversions. However, the main challenges in implementing this strategy are dynamic changes in social media algorithms and the need to create content that is innovative and relevant to trends. Therefore, companies need to carry out regular evaluations and strategy adjustments to remain competitive in digital marketing.